Polytechnic students in Mexico and their perceptions about the fears that hinder them to undertake entrepreneurship - Hernández Herrera, Claudia Alejandra; Pérez Hernández, María del Pilar Monserrat (IE Revista de Investigación Educativa de la REDIECH, 2021)
Entrepreneurship allows economy growth of countries, creates jobs, develops new technology and increases the standard of living and well-being of citizens. The objective of this article was to analyze the perceptions that young polytechnics students have in relation to the phenomenon of entrepreneurship and its possible obstacles. It is a cross-sectional study; data was obtained through a questionnaire, and 9,626 students from the three educational levels at Instituto Politécnico Nacional participated. A descriptive study was carried out and generalized linear models that allow multivariate analysis were used. It was found that only 15% of the students have participated in entrepreneurial activities, in addition to that only 25% of young people from secondary and higher education have had businesses (but only 11% of these continue to operate). The fear of failure was detected with greater prevalence in women who study high school or undergraduate, coupled with the fact that the feeling of failure was presented in young people who come from families in vulnerable sectors. It is concluded that the institute must pay greater attention to women to train them, as well as to maintain and reinforce its actions aimed at business education and entrepreneurship training.